Design characterization of Erbium-Doped Fiber Ring Laser using a circulator and filter for C and L band amplification - Brahma, Debolina; Goswami, Sanchita; Biswas, Sambhunath (Photonics Letters of Poland, 2014)
Design characterization of a wavelength division multiplexed erbium doped fiber ring laser using an ITU-T signal source at ?30dBm/channel input signal level, a splitter, 980nm and 1480nm pumping lasers in bidirectional pumping scheme with 250mW pump powers and two double pass EDFAs with 10m and 20m lengths at room temperature, a circulator and a gain flattening filter (GFF). An average gain of 34.45dB and noise figure of 8dB (maxima) is on optimization to provide a uniform gain over 70nm. Full Text: PDF References S.W. Harun, H. Ahmad, "Gain-clamped two-stage L-band EDFA with a FBG laser in second stage", Opt. Laser Techn. 35, 645 (2003). CrossRef C.L. Chang, L. Wang, Y.J. Chiang, "A dual pumped double-pass L-band EDFA with high gain and low noise", Opt. Comm. 267, 108 (2006). CrossRef N.M. Yusoff, A.F. Abas, S. Hitam, M.A. Mahdi, "Dual-stage L-band erbium-doped fiber amplifier with distributed pumping from single pump laser", Opt. Comm. 285, 1383 (2012). CrossRef R. Anthony, R. Lahiri, S.N. Biswas, "Study of Power Conversion Efficiency of a Novel Hybrid L-Band Erbium Doped Fiber Amplifier", Inter. J. Comp. App. 44(14), 1 (2012). CrossRef J.H. Lee, W.J. Lee, N. Park, "Comparative study on temperature-dependent multichannel gain and noise figure distortion for 1.48- and 0.98-?m pumped EDFAs", IEEE Phot. Techn. Lett. 10(12), 1721 (1998). CrossRef R. Anthony, S.N. Biswas, "Temperature Dependent Gain Analysis of a Cascaded C-Band EDFA DWDM Network", Elseviers Proc. Techn. 4, 92 (2012). CrossRef A.H.M. Husein, F.I. El-Nahal, "Optimizing the EDFA gain for WDM lightwave system with temperature dependency", Optik 123, 586 (2012). CrossRef Y.B. Lu, P.L. Chu, A. Alphones, P. Schum, "A 105-nm ultrawide-band gain-flattened amplifier combining C- and L-band dual-core EDFAs in a parallel configuration", IEEE Photon. Technol. Lett. 16(7), 1640 (2004). CrossRef S.K. Liaw, C.K. Huang, Y. L. Hsiao, "Parallel-type C+L band hybrid amplifier pumped by 1480 nm laser diodes", Laser Phys. Lett. 5(7), 543 (2008). CrossRef R.K. Varshney, P.J. Lemaire, J.B. Judkins, V. Bhatia, T. Erdogan, J.E. Sipe, "Long-period fiber gratings as band-rejection filters", IEEE J. Lightwave Techn. 14, 58 (1996). CrossRef J.Y. Pan, M.A. Ab, A.F. Elsefare, R. E. Wagener, "Multiwavelength fiber-amplifier cascades with equalization employing Mach-Zehnder optical filter", IEEE Photon. Technol. Lett. 7, 1501 (1995). CrossRef S. Pain, M. Biswas, S. Biswas, "Gain Flattening and Noise Figure Analysis of EDFA WDM Configuration for L-band Optical Communication using Wavelength Selective Attenuator", Phot. Lett. Poland 5(3), 106 (2013). CrossRef C.R. Giles, E. Desurvire, "Modeling erbium-doped fiber amplifiers", IEEE J. Lightwave Techn, 9(2), 271 (1991). CrossRef J. Kemtchou, M. Dhamel, P. Lecoy, "Gain temperature dependence of erbium-doped silica and fluoride fiber amplifiers in multichannel wavelength-multiplexed transmission systems", IEEE J. Lightwave Techn. 15(11), 2083 (1997). CrossRef